Determination of the Human Development Index: Panel Data Analysis of Per Capita GRDP, Open Unemployment Rate, and Health Complaints in Java Island 2015-2024 - Sri Dewi Miladiyah; Rosidah Rosidah; Tarudi Tarudi; Syaeful Bakhri; Abdul Aziz (Universitas KH. Abdul Chalim Mojokerto, 2026)
Determination of the Human Development Index: Panel Data Analysis of Per Capita GRDP, Open Unemployment Rate, and Health Complaints in Java Island 2015–2024. This study aims to analyze the influence of GRDP per capita, Open Unemployment Rate (TPT), and Health Complaints on the Human Development Index (HDI) in six provinces in Java Island during the period 2015–2024. Using a quantitative approach based on panel data regression analysis, this study processed 60 observation units sourced from the official publication of the Central Statistics Agency (BPS). The results of the model selection test through the Chow Test and Hausman Test determined the Fixed Effect Model (FEM) as the best estimation model. The results of the simultaneous test showed that the three independent variables together had a significant effect on the HDI (F = 641.0955; prob. = 0.0000) with an Adjusted R-squared value of 0.9886, which means that 98.86% of the variation in the HDI in Java Island can be explained by the model. Partially, only GRDP per capita has a positive and significant effect on the HDI (coefficient = 13.3333; prob. = 0.0000), confirming that regional economic capacity is the dominant determinant of human development in Java. Meanwhile, Health Complaints (prob. = 0.6413) and TPT (prob. = 0.5637) do not have a significant effect on the HDI, which is thought to be caused by the subjective-perceptual nature of health variable measurements and the effectiveness of social safety net programs in mitigating the impact of unemployment. This study recommends inclusive and equitable economic growth policies, strengthening primary health services, and optimizing social financial instruments to accelerate the achievement of sustainable human development in Java.